Antillipeltis, a new genus of Antillean Trogossitidae (Coleoptera: Cleroidea) with a key to the Cleroidea - Lawrence, John F.; Leschen, Richard A.b.; Ślipiński, Adam (Zootaxa, 2014)
Antillipeltis gen. nov. is described based on the following six new extant species and two new fossil species from Hispaniola and Puerto Rico: A. alleni sp. nov. (Dominican Republic, Miocene), A. darlingtoni sp. nov. (Haiti), A. iviei sp. nov. (Dominican Republic, Miocene), A. maculata sp. nov. (Dominican Republic), A. minuta sp. nov. (Dominican Republic), A. nitida sp. nov. (Puerto Rico), A. portoricensis sp. nov. (Puerto Rico), and A. pubescens sp. nov. (Dominican Republic). The genus is placed in Cleroidea, as currently delimited, based on the presence of a distinctive type of aedeagus occurring primarily in this superfamily, plus a combination of features excluding it from other cucujiform superfamilies. Within Cleroidea, the genus is tenatively placed in the family Trogossitidae and subfamily Lophocaterinae, but it differs from all other Trogossitidae in the presence of ventral membranous lobes with adhesive setae on tarsomeres 1–4 and in a combination of 9-segmented antennae, weak 3-segmented antennal club consisting of slightly elongate antenomeres, lack of postcoxal processes on the pronotal hypomera, and unique leg modifications. A key is provided for major groups of Cleroidea and all described genera of Peltinae and Lophocaterinae, with the exception of Rentoniini, based in part on the literature and in part on dissections of adult males. Antillipeltis is one of three endemic West Indian genera of Coleoptera that is both extant and known from Dominican amber.